Biotech industry : a global, economic, and financing overview - Bergeron, Bryan P. (Wiley, 2004)
Biotech Industry: A Global, Economic, and Financing Overview provides a thorough look at the current state of the biotechnology industry, including where major research is being conducted, where it's being applied, and where money and intellectual capital are flowing.